Studi Literatur: Efektivitas Model Kesiapsiagaan Bencana di Komunitas - I Made Moh. Yanuar Saifudin; Ni Luh Seri Astuti; Novida Prima Wijayanti; Marsha Yoke Nancy; Ahmad Firdaus; Uki Noviana; Sri Warsini (Jurnal Kesehatan Manarang, 2021)
Natural disasters occur all over the world and have massive effects. The impact of natural disasters has prompted various studies to find out the effects of a better mitigation and preparedness phase on individuals and communities in reducing the number of victims. Although revious literature are available that discuss disaster preparedness, studies that specifically assess the effectiveness of community-based disaster preparedness training are not available yet. This study aimed to identify effectiveness of community-based disaster preparedness training and which communication media are effective for use in disaster management in society. The literature reviews were conducted using the PRISMA model. The articles were collected from 4 journal databases, including EBSCO, Science Direct, Scopus dan ProQuest. Quality of each articles were assessed by Crowe Critical Appraisal Tool (CCAT). We identified a total of 3 studies. From the data extraction, 4 types of interventions were obtained in increasing disaster preparedness including phone-based intervention, printed media intervention, peer-mentored preparedness (PM-Prep) program and small group discussion intervention. The effectiveness of community-based disaster preparedness training is evidence that is needed to be applied in various countries due to the high prevalence of natural disasters worldwide.